2019
DOI: 10.14746/ssllt.2019.9.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Using drama activities to teach beginner’s French to Chinese students at a tertiary institution in Hong Kong: An exploratory case study

Abstract: The exam-oriented education system in Hong Kong has created a language learning environment that is largely confined to traditional classroom settings, which may not take best advantage of students’ abilities to relate what they have learnt in class to real-life scenarios. Such learning environments may have implications for the way second language learners learn a new language. Numerous studies suggest that drama activities used in language classrooms can enhance second language learning. These studies put fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similarly, the use of costumes has been shown to have a positive impact on learners' perceptions of their own language use, increasing their sense of competence (DeCoursey, 2014). Other studies have revealed that drama exercises helped to reduce student anxiety and increase students' confidence, motivation, and flow experience (e.g., Abenoja & DeCoursey, 2019;İşigüzel, 2020). Teachers have also found drama-based instruction to help students develop empathy (Toksun, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Similarly, the use of costumes has been shown to have a positive impact on learners' perceptions of their own language use, increasing their sense of competence (DeCoursey, 2014). Other studies have revealed that drama exercises helped to reduce student anxiety and increase students' confidence, motivation, and flow experience (e.g., Abenoja & DeCoursey, 2019;İşigüzel, 2020). Teachers have also found drama-based instruction to help students develop empathy (Toksun, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, drama-based pedagogy has gained considerable research interest in the field of second language (L2) education (Stinson & Freebody, 2006;Piazzoli, 2010;Abenoza & Decoursey, 2019;Alam, Karim & Ahmad, 2020;Altweissi & Maaytah, 2022). Such shift trends indicate how every type of drama in second language (L2) instruction has value because it creates circumstances for cross-linguistic interactions and promotes genuine communication between teachers and students.…”
Section: Introductionmentioning
confidence: 99%